Arabicization or Englishization of higher education in the Arab world? Controversies, policies and realities - Abdel Latif, Muhammad M. M.; Alhamad, Majed M. (Frontiers in Psychology, 2023)
Though there have been many calls for the Arabicization versus Englishization of higher education in the Arab world, no previous work seems to have comprehensively covered these calls and their outcomes in the region. In this paper, we review literature on the following four main pertinent issues: a) the arguments for and against the Arabicization versus Englishization of higher education; b) Arabicization attempts of higher education in the Arab world; b) current Englishization policies and orientations of Arab higher education systems; and d) realities of EMI practices in Arab universities. We conclude that higher education Arabicization movements in the Arab world have not brought about their desired outcomes due to some barriers, whereas Englishization policies and practices have increasingly expanded in the region in the last three decades. We end the paper with discussing the implications of the review.